Landscape Design of Territories Public Buildings (Journal of Architectural Design, 2022)
Modern cities host a large number of different public buildings. Each of them occupies a certain territory on which there are plots, sometimes very large, free from construction. Landscaping and landscaping of such areas are carried out according to the principles of the formation of a garden related to a particular public building